Math, asked by ay6111188, 2 months ago

Lim x ➡️ 3 , √x+1 -2 / √x+6 -3 ,what is the value of x ?

Answers

Answered by anindyaadhikari13
30

\textsf{\large{\underline{Solution}:}}

We have to evaluate:

 = \displaystyle \rm \lim_{x \to3} \bigg( \dfrac{ \sqrt{x + 1} - 2}{ \sqrt{x + 6} - 3 } \bigg)

On evaluating this limit, we will get an indeterminate form. So, we have to apply L'Hospital's rule.

Applying L'Hospital's rule, we get:

 = \displaystyle \rm \lim_{x \to3} \bigg( \dfrac{  \dfrac{d}{dx} (\sqrt{x + 1} - 2)}{ \dfrac{d}{dx}  (\sqrt{x + 6} - 3) } \bigg)

 = \displaystyle \rm \lim_{x \to3} \bigg( \dfrac{ \dfrac{1}{2 \sqrt{x +1 } } }{ \dfrac{1}{2 \sqrt{x + 6} }  } \bigg)

 = \displaystyle \rm \lim_{x \to3} \bigg( \dfrac{ \sqrt{x + 6} }{ \sqrt{x + 1} } \bigg)

Put x = 3, we get:

 = \displaystyle \rm\dfrac{ \sqrt{3+ 6} }{ \sqrt{3 + 1} }

 = \displaystyle \rm\dfrac{ \sqrt{9} }{ \sqrt{4} }

 \rm =  \dfrac{3}{2}

Therefore:

: \longmapsto  \displaystyle \rm \lim_{x \to3} \bigg( \dfrac{ \sqrt{x + 1} - 2}{ \sqrt{x + 6} - 3 } \bigg) =  \dfrac{3}{2}

\textsf{\large{\underline{Learn More}:}}

 \rm 1. \: \: \dfrac{d}{dx} \sin(x)  =  \cos(x)

 \rm 2. \: \: \dfrac{d}{dx} \cos(x)  =   - \sin(x)

 \rm 3. \: \: \dfrac{d}{dx} \tan(x)  =  \sec^{2} (x)

 \rm 4. \: \: \dfrac{d}{dx} \cot(x)  =  -  \csc^{2} (x)

 \rm 5. \: \: \dfrac{d}{dx} \sec(x) =  \tan(x) \cdot \sec(x)

 \rm 6. \: \: \dfrac{d}{dx} \csc(x) =   - \cot(x) \cdot \csc(x)

 \rm 7. \:  \:  \dfrac{d}{dx} {x}^{n}  = n {x}^{n - 1}

 \rm 8. \:  \:  \dfrac{d}{dx}c=0

 \rm 9. \:  \:  \dfrac{d}{dx} {e}^{x} = {e}^{x}

 \rm 10. \:  \:  \dfrac{d}{dx} {a}^{x} = {a}^{x} \:  ln(a)

Answered by SANDHIVA1974
2

Step-by-step explanation:

]\textsf{\large{\underline{Solution}:}}

We have to evaluate:

 = \displaystyle \rm \lim_{x \to3} \bigg( \dfrac{ \sqrt{x + 1} - 2}{ \sqrt{x + 6} - 3 } \bigg)

On evaluating this limit, we will get an indeterminate form. So, we have to apply L'Hospital's rule.

Applying L'Hospital's rule, we get:

 = \displaystyle \rm \lim_{x \to3} \bigg( \dfrac{  \dfrac{d}{dx} (\sqrt{x + 1} - 2)}{ \dfrac{d}{dx}  (\sqrt{x + 6} - 3) } \bigg)

 = \displaystyle \rm \lim_{x \to3} \bigg( \dfrac{ \dfrac{1}{2 \sqrt{x +1 } } }{ \dfrac{1}{2 \sqrt{x + 6} }  } \bigg)

 = \displaystyle \rm \lim_{x \to3} \bigg( \dfrac{ \sqrt{x + 6} }{ \sqrt{x + 1} } \bigg)

Put x = 3, we get:

 = \displaystyle \rm\dfrac{ \sqrt{3+ 6} }{ \sqrt{3 + 1} }

 = \displaystyle \rm\dfrac{ \sqrt{9} }{ \sqrt{4} }

 \rm =  \dfrac{3}{2}

Therefore:

: \longmapsto  \displaystyle \rm \lim_{x \to3} \bigg( \dfrac{ \sqrt{x + 1} - 2}{ \sqrt{x + 6} - 3 } \bigg) =  \dfrac{3}{2}

\textsf{\large{\underline{Learn More}:}}

 \rm 1. \: \: \dfrac{d}{dx} \sin(x)  =  \cos(x)

 \rm 2. \: \: \dfrac{d}{dx} \cos(x)  =   - \sin(x)

 \rm 3. \: \: \dfrac{d}{dx} \tan(x)  =  \sec^{2} (x)

 \rm 4. \: \: \dfrac{d}{dx} \cot(x)  =  -  \csc^{2} (x)

 \rm 5. \: \: \dfrac{d}{dx} \sec(x) =  \tan(x) \cdot \sec(x)

 \rm 6. \: \: \dfrac{d}{dx} \csc(x) =   - \cot(x) \cdot \csc(x)

 \rm 7. \:  \:  \dfrac{d}{dx} {x}^{n}  = n {x}^{n - 1}

 \rm 8. \:  \:  \dfrac{d}{dx}c=0

 \rm 9. \:  \:  \dfrac{d}{dx} {e}^{x} = {e}^{x}

 \rm 10. \:  \:  \dfrac{d}{dx} {a}^{x} = {a}^{x} \:  ln(a) [/tex]

Similar questions